Comparison of Phoenix and VITEK 2 Extended-Spectrum-β-Lactamase Detection Tests for Analysis of Escherichia coli and Klebsiella Isolates with Well-Characterized β-Lactamases - Thomson, Kenneth S. (American Society for Microbiology, 2007)
The VITEK 2 and Phoenix extended-spectrum β-lactamase (ESBL) detection systems, which comprise confirmatory tests and expert systems, were evaluated for their ability to discriminate between 102 well-characterized strains of ESBL-positive or -negative Escherichia coli, Klebsiella pneumoniae, and Klebsiella oxytoca. At least 38 distinct ESBLs were included. The strains were chosen to include some known to cause false-positive and false-negative CLSI ESBL confirmatory test results. Therefore, enzyme characterizations, rather than CLSI tests, were the reference methods for the Phoenix and VITEK 2 evaluations. A third arm of the study was conducted with the Phoenix test using two normally inactive expert rules intended to enhance ESBL detection, in addition to using the currently available software. The Phoenix ESBL confirmatory test and unmodified expert system exhibited 96% sensitivity and 81% specificity for ESBL detection. Activation of the two additional rules increased sensitivity to 99% but reduced the specificity to 58%. The VITEK 2 ESBL confirmatory test exhibited 91% sensitivity, which was reduced to 89% sensitivity by its expert system, while its specificity was 85%. Many of the expert system interpretations of both instruments were helpful, but some were suboptimal. The VITEK 2 expert system was potentially more frustrating because it provided more inconclusive interpretations of the results. Considering the high degree of diagnostic difficulty posed by the strains, both ESBL confirmatory tests were highly sensitive. The expert systems of both instruments require modification to update and enhance their utility.